Reconsidering success for an integrated family dependency treatment court. (July 2020) - Moore, Kathleen; Sharp, Amanda; Alitz, Paige; Yampolskaya, Svetlana; Kleinman, Mary; Carlson, Melissa; Argerious, Alexa
Highlights: Substance use treatment. Child welfare. Family Dependency Treatment Court (FDTC) Permanent placement and reunification. Abstract: Parental alcohol and substance use is a significant contributing factor for child removal. Family Dependency Treatment Courts (FDTCs) offer an interagency approach to treating parental substance abuse after child removal and addressing the comprehensive needs of children and their parents, with the ultimate goal of family reunification. There is a dearth of FDTC evaluation studies that examine permanent placement outcomes s as compared to other traditional family courts. The current study used a matched sample of 72 FDTC and dependency court participants to assess whether participation in the FDTC program is associated with an increased chance to achieve permanency and a shorter time to permanency compared to families who were brought before the dependency court. Results indicated no significant difference between groups when time to reunification was examined. However, once families were enrolled in FDTC, they achieved permanent placement faster than the comparison group. These results put question to the guidelines and prior research that specify preference for reunification over other permanent placements as well as highlight where court procedures may be streamlined in order to reduce the time a child spends in transitional placement. Implications of these findings for research, policy, and practice are also discussed and future research is suggested.